Acute effects of citrulline supplementation on high-intensity strength and power performance: A systematic review and meta-analysis - Trexler, E. T.; Persky, A. M.; Ryan, E. D.; Schwartz, T. A.; Stoner, L.; Smith-Ryan, A. E. (Sports Medicine, 2019)
Background: Citrulline is an increasingly common dietary supplement that is thought to enhance exercise performance by increasing nitric oxide production. In the last 5 years, several studies have investigated the effects of citrulline supplements on strength and power outcomes, with mixed results reported. To date, the current authors are unaware of any attempts to systematically review this emerging body of literature. Objective: The current study sought to conduct a systematic review and meta-analysis of the literature describing the effects of citrulline supplementation on strength and power outcomes. Methods: A comprehensive, systematic search of three prominent research databases was performed to find peer-reviewed, English language, original research studies evaluating the effects of citrulline supplementation on indices of high-intensity exercise performance in healthy men and women. Outcomes included strength and power variables from performance tests involving multiple repetitive muscle actions of large muscle groups, consisting of either resistance training sets or sprints lasting 30 s or less. Tests involving isolated actions of small muscle groups or isolated attempts of single-jump tasks were not included for analysis due to differences in metabolic requirements. Studies were excluded from consideration if they lacked a placebo condition for comparison, were carried out in clinical populations, provided a citrulline dose of less than 3 g, provided the citrulline dose less than 30 min prior to exercise testing, or combined the citrulline ingredient with creatine, caffeine, nitrate, or other ergogenic ingredients. Results: Twelve studies, consisting of 13 total independent samples (n = 198 participants), met the inclusion criteria. Between-study variance, heterogeneity, and inconsistency across studies were low (Cochrane`s Q = 6.9, p = 0.86; t2 = 0.0 [0.0, 0.08], I2 = 0.0 [0.0, 40.0]), and no funnel plot asymmetry was present. Results of the meta-analysis identified a significant benefit for citrulline compared to placebo treatments (p = 0.036), with a small pooled standardized mean difference (SMD; Hedges` G) of 0.20 (95% confidence interval 0.01-0.39). Conclusion: The effect size was small (0.20), and confidence intervals for each individual study crossed the line of null effect. However, the results may be relevant to high-level athletes, in which competitive outcomes are decided by small margins. Further research is encouraged to fully elucidate the effects of potential moderating study characteristics, such as the form of citrulline supplement, citrulline dose, sex, age, and strength versus power tasks.